The influence of experience and confidence on the health management of dairy goat (Case study: “Simpay Tampomas Farmer Group” Village Cilengkrang, Cimalaka District of Sumedang, West Java-Indonesia) - Hartady, Tyagita; Widyastuti, Rini (ARSHI Veterinary Letters, 2018)
Dairy goat is profitable object since the productivity is relatively brief, easy in maintenance and does not require much investment. Dairy goat become one of the important commodity for farmers in the village Cilengkrang, Cimalaka District of Sumedang. This study used a qualitative approach where 18 farmers who become interviewees. Collected data were observed and compared with the evaluation on the participants’ routine. The majority farmers are depending on individual experiences and conclusions without related guidance and supported references of diseases and procedures in nurturing dairy goats (61.1%), while the rest are consulting the problem to the vet or the group (83,3%). Some of them used the conventional treatment. However, when the condition of sick animal never improved, only 83,3% of farmers who contact veterinarian and the rest would prefer sell the animal in the market. It can be concluded that the majority farmers in the village, has experienced to overcome certain diseases of dairy goats. Nevertheless, the knowledge and sources of supporting references are still limited that affect to the use of inappropriate traditional herbs or regular human medicines from nearby stalls is still relatively high, so the awareness and knowledge of breeders about health management of dairy goat of breeders needs to be improved.